2014
DOI: 10.4161/15548627.2014.984274
|View full text |Cite
|
Sign up to set email alerts
|

New horizons in schizophrenia treatment: autophagy protection is coupled with behavioral improvements in a mouse model of schizophrenia

Abstract: Autophagy plays a key role in the pathophysiology of schizophrenia as manifested by a 40% decrease in BECN1/Beclin 1 mRNA in postmortem hippocampal tissues relative to controls. This decrease was coupled with the deregulation of the essential ADNP (activity-dependent neuroprotector homeobox), a binding partner of MAP1LC3B/LC3B (microtubule-associated protein 1 light chain 3 β) another major constituent of autophagy. The drug candidate NAP (davunetide), a peptide fragment from ADNP, enhanced the ADNP-LC3B inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 59 publications
2
54
0
Order By: Relevance
“…Administration of NAP, a peptide fragment of ADNP also known as davunetide, enhanced the ADNP-LC3 interaction and reversed the decrease in hippocampal BECN1 mRNA levels in a mouse model of schizophrenia (MAP6-deficiency) (Merenlender-Wagner et al, 2014). Normalization of BECN1 expression by NAP led to positive outcomes in the behavioral phenotype of MAP6-deficient mice.…”
Section: Autophagy and Schizophrenia: Understanding The Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of NAP, a peptide fragment of ADNP also known as davunetide, enhanced the ADNP-LC3 interaction and reversed the decrease in hippocampal BECN1 mRNA levels in a mouse model of schizophrenia (MAP6-deficiency) (Merenlender-Wagner et al, 2014). Normalization of BECN1 expression by NAP led to positive outcomes in the behavioral phenotype of MAP6-deficient mice.…”
Section: Autophagy and Schizophrenia: Understanding The Mechanismmentioning
confidence: 99%
“…The changes observed in treated animals included decreased hyper-locomotion and cognitive deficits as measured by the object recognition test. The combination of NAP with clozapine, an FDA-approved antipsychotic used in refractory schizophrenia, resulted in complete normalization of behavioral outcomes (Merenlender-Wagner et al, 2014). These studies highlight a potential role for NAP-mediated autophagy rescue in mouse models of schizophrenia and suggest a new therapeutic strategy of supplying adjuvant treatment along with antipsychotic medication to bolster the efficacy of therapy.…”
Section: Autophagy and Schizophrenia: Understanding The Mechanismmentioning
confidence: 99%
“…Regarding schizophrenia, we showed that ADNP is linked with the regulation of autophagy, and we further showed that this process is disrupted in schizophrenia and corrected by NAP treatment (Merenlender-Wagner et al 2014, 2015. In this respect, an impaired gut microbiome inhibits the autophagy-mediated protein clearance process and a distinct gut microbiome composition can change the neurotransmitter levels in the brain through the vagal afferent fibers also pertinent for AD (Bostanciklioglu 2019).…”
Section: Sniffing ɵMe (S)-cupmentioning
confidence: 72%
“…Administration of NAP, a peptide fragment of ADNP, enhances the activity of ADNP-LC3, a key component of the autophagic machinery interaction and reverses the decrease in hippocampal BECN1 mRNA levels in a mouse model of schizophrenia. The combination of NAP with clozapine results in complete normalization of behavioral outcomes (Merenlender-Wagner et al, 2014).…”
Section: Implication In Mammalsmentioning
confidence: 99%